Emerging technologies revolutionizing the pork industry: A boost in the Peruvian pork sector - Rodríguez Silva, Lady Elizabeth; Areli Natalia, Zeña Villanueva; Zúñiga Abregú, Romi Rubí (LACCEI, 2025)
The objective of this research was to evaluate the influence of the use of emerging technologies in the improvement of pig farming in Peru by 2024. A non-experimental methodological design was used with a qualitative approach and a descriptive scope, using the deductive method and statistical data search techniques and online documentary review. The main results indicated that genomic selection and genetic editing increased production efficiency and genetic quality of pigs by 15-20% in countries such as the European Union and the United States. In addition, technologies based on artificial intelligence, such as FertiBoar and phenotyping, improved reproductive efficiency in Brazil by 18% and reduced operating costs by 10-12%. Likewise, the use of dry and wet scrubbers achieved emission reductions of up to 90% in the European Union, improving animal and environmental welfare. Automation in the evaluation of animal aplomb and behavior allowed a more efficient selection of breeding animals in the United States. The findings suggested that the adoption of these technologies in Peru could have significantly improved the competitiveness of pig farming, optimizing production and meeting quality and sustainability standards. The implementation of these innovations could have reduced production costs by up to 15-20% and improved genetic quality, facilitating entry into international markets that value sustainability and efficiency.